Following Gaze: Gaze-Following Behavior as a Window into Social Cognition - Shepherd, Stephen V. (Frontiers in Integrative Neuroscience, 2010)
In general, individuals look where they attend and next intend to act. Many animals, including our own species, use observed gaze as a deictic ("pointing") cue to guide behavior. Among humans, these responses are reflexive and pervasive: they arise within a fraction of a second, act independently of task relevance, and appear to undergird our initial development of language and theory of mind. Human and nonhuman animals appear to share basic gaze-following behaviors, suggesting the foundations of human social cognition may also be present in nonhuman brains.